PENGAWASAN DAN PENDAMPINGAN KERJA UKS DALAM MELAKUKAN PELAYANAN DI SMP ISLAM TERPADU AL-ULUM MEDAN - Wisnu Fadillah; Budi; Anysah Daulay; Ananda Taharah; Dwi Asri; Irawati Tarihoran (CV. Arsy Persada Quality, 2024)
This research aims to determine the performance of UKS services that run effectively and provide UKS assistance to produce healthy students. The UKS service aims to provide a place of treatment and recovery for sick people at this school. This research was conducted on UKS coordinator supervisors and Al-Ulum Integrated Islamic Middle School students. The research method used was observing the UKS room's condition, the UKS's needs, and all the facilities in the UKS room. The interview method was carried out with the UKS coordinator, regarding his supervision, assistance, and services. The results of this research indicate that the UKS is permanent and is currently undergoing renovation. This UKS also collaborates with the Community Health Center to improve assistance and supervision of UKS work in services. Al-Ulum Middle School has two UKS consisting of special rooms for men and women. Then, in this room, there are four rooms, and each room is guarded by three people who take turns on duty every day. There are four medical equipment available in each room, and medical equipment (P3K). Al-Ulum UKS supervision and services are by school UKS standards.